Answer: The linear expression is x+4.
Step-by-step explanation: We are given to create a linear expression and also to create equivalent expressions and explain your other expressions are equivalent to the original one.
Let the linear expression be
![m=x+4.](https://img.qammunity.org/2020/formulas/mathematics/high-school/inphnajctjdh8by7o0sdywpn3f88m81ox1.png)
And also, equivalent expressions be
![n=(x^2+6x+8)/(x+2),\\\\o=(x^2-16)/(x-4),\\\\p=(x^2+x-12)/(x-3).](https://img.qammunity.org/2020/formulas/mathematics/high-school/15d4i4bmayu5bon9rwempyjos5ovqakj7q.png)
Since,
![n=(x^2+6x+8)/(x+2)=((x+4)(x+2))/(x+2)=x+4=m,\\\\o=(x^2-16)/(x-4)=((x+4)(x-4))/(x-4)=x+4=m,\\\\p=(x^2+x-12)/(x-3)=((x+4)(x-3))/(x-3)=x+4=m.](https://img.qammunity.org/2020/formulas/mathematics/high-school/jhowuqndaebzcfcc4kry4wwiz3ll0ki9sw.png)
Thus, these three expressions 'n', 'o' and 'p' are equivalent to the original expression 'm'.